A Cross-sectional Study of Nurses’ Perception Toward Utilization and Barriers of Electronic Health Record - Alboliteeh, Mohammad (Makara Journal of Health Research, 2022)
Background: The utilization of electronic health records (EHRs) is crucial. This study aimed to determine the perception of nurses on the utilization and barriers to the use of EHRs. Methods: This descriptive cross-sectional study on 327 participants was conducted at the government hospitals of Hail City that use EHRs. Data collection was conducted between March and April 2022. The adapted questionnaire was used to collect the data. Results: Nurses perceived EHRs as useful (5.76 ± 1.71), easy to use (4.74 ± 1.56), and intend to use (5.85 ± 1.81). Sex had no effect on perceived usefulness (p > 0.671), perceived ease of use (p > 0.605), or intention to use (p > 0.880). A significant difference was found in the perceived usefulness based on age (p = 0.045). On training, a significant difference was noted in perceived usefulness (p = 0.039) and intention to use (p = 0.007). Conclusions: An EHR system is useful and easy to use, and nurses intended to use it. Sex had no effect on perceived usefulness, perceived ease of use, or intention to use. Age showed a significant difference in perceived usefulness. Moreover, training has a significant difference in perceived usefulness and intention to use. Policymakers can use these findings to create a program that targets the needs of nurses so that they can fully utilize EHRs.